Governance for development - Vittal, N. (2004)
Good governance will be the engine for development in a liberalised economy. The two elements of honesty and transparency are needed to ensure governance for development. But the one single factor that has nullified the whole process of planned economic development is the rampant corruption in our system. The corruption is anti-economic development, anti-poor and anti-national, and the supreme importance of checking corruption is therefore obvious. This is all the more so especially when we consider that the central focus of entire planning process is on removal of poverty, and alleviating the conditions of the poor. The ability to use governance as an effective tool for economic development will dependent on oor success to effectively check the corruption. - Reproduced.
Keywords: Good governance